Invasive brain stimulation in the treatment of psychiatric illness: proposed indications and approaches = Invasive Hirnstimulation zur Behandlung von psychiatrischen Erkrankungen : Vorschläge zur Indikationsstellung und zum praktischen Vorgehen - Schläpfer, Thomas; Meyer-Lindenberg, Andreas; Synofzik, Matthis; Visser-Vandewalle, Veerle; Voges, Jürgen; Coenen, Volker Arnd (Deutsches Ärzteblatt, 2021)
Background: Drugs, psychotherapy, and other treatment modalities are effective for many patients with mental illness. Nonetheless, many patients do not achieve a total remission with the currently available interventions, and the recurrence rates are high. As part of the ongoing search for further treatment options for refractory disorders, there is renewed interest in focal neuromodulatory techniques, including invasive ones, and deep brain stimulation (DBS) in particular. Methods: In this review article, a group consisting of neurosurgeons, psychiatrists, and one practicing ethicist/neurologist summarizes the main aspects of the use of DBS to treat mental illness and offers recommendations on its indications and practical implementation. Results: The efficacy of DBS against mental illness has not been confirmed in the randomized, controlled trials (RCTs) that have been published to date. This may be because the follow-up times were too short. In contrast to the negative RCTs, case series have indeed shown a positive effect of DBS on severe depression, but this effect can only be seen several months after the operation. Conclusion: DBS may be a therapeutic option for selected patients with otherwise intractable mental illness. Patients should only be treated in the setting of clinical trials. RCTs with longer follow-up times must be conducted in order to substantiate, if possible, the promising evidence that has been found in case series.
Gesehen am 30.04.2021